A bibliometric analysis on cloud computing literature development - Teh, Raymond; Subramaniam, Anusuiya (Penerbit UTM Press, 2023)
The purpose of this paper is to present a bibliometric analysis on cloud computing literature development since year 2008. A systematic search strategy was carried out through Scopus as the single electronic citation database in this bibliometric analysis. The findings reveal that the publication of cloud computing has been steadily maintained at the same rate for last few years except in 2020 which could be due to higher concentration on COVID related publications. Besides that, the cloud computing publications were reduced could be due to work from home situation which pull down the work efficiency and another possibility is cloud computing publications have started to decline and overtaken by other technologies due to the interest and demand from the academics and market, but this must be observed in next following 2 to 3 years to confirm on this. Precisely, the finding of this bibliometric analysis shows that countries with higher cloud computing literature publications tends to have higher cloud computing growth rate which implies that local government and related bodies are playing an important role to facilitate the technology awareness and transformation. This study contributes to cloud computing research by providing holistic insights of its literature development since 2018 by understanding its development, growth pattern, and contributions by the topmost affiliations/institutions, countries, authors, publishers in this area. In future, bibliometric analysis on cloud computing could be extended to other citation databases as this study is only referring to single citation database.